Analisis Praktek Bisnis dan Pendapatan UMKM Akibat Covid-19 Di Kecamatan Tamalanrea Kota Makassar - Muhamad Hasan; Andi Bintang Balele; Mattarima Mattarima (Universitas 17 Agustus 1945 Semarang, 2022)
This study aims to determine the impact of COVID-19 toword buses and the income of Micro, Small and Medium Enterprises (MSMEs) in the Tamalanrea sub-district, Makassar City. This research is a qualitative research with qualitative descriptive analysis method using data collection such as documentation and theoretical studies. Based one the results of research in the Tamalanrea District, Makassar City. COVID-19 has had a significant impact on the culinary trade business, the culinary industry and handicrafts, SMEs have also experienced a decline income during the COVID-19 pandemic and some are even threantened with bankruptcy. The government must make policies that can help the economy of SMEs in the midset of the COVID-19 pandemic. In this way, ME actors are able tu survive in their respective business despite the decline in income.